Key challenges in providing assisted dying in Belgium: a qualitative analysis of health professionals’ experiences - Madeleine Archer; Lindy Willmott; Kenneth Chambaere; Luc Deliens; Ben P. White (Palliative Care and Social Practice)
Background: Assisted dying or ‘euthanasia’ has been legal in Belgium since 2002. Extensive research has been conducted which investigates Belgian euthanasia practice, however, the current challenges that health professionals face when providing euthanasia are not well known. This knowledge is important for evaluating the current system, especially in light of recent developments in Belgian euthanasia law and practice including judicial decisions, legislative amendments and research highlighting the complexity of its governing regulatory framework. Objectives: This study investigates the key challenges that health professionals experience when providing euthanasia in Belgium. Design: A qualitative interview study with reflexive thematic analysis. Methods: Twenty interviews were conducted between September 2022 and March 2024 using Microsoft Teams videoconferencing. Eligible participants were physicians and nurses who spoke English or Dutch and who had been involved in the euthanasia assessment of at least two patients in the past year. Results: Four themes were generated: (1) the framing of the euthanasia legislation poses challenges; (2) providing euthanasia can place considerable burdens on health professionals; (3) clashing views about euthanasia can hamper opportunities for balanced discussions and (4) euthanasia and processes relating to euthanasia are not always well-understood. Conclusion: This study highlights the numerous and varied challenges physicians and nurses experience when providing euthanasia in Belgium, even 20 years after its law passing. This study contributes to a wider understanding of universal challenges associated with providing assisted dying and sheds light on issues specific to Belgium. The results provide an opportunity for policymakers to take action to better support providers to manage these challenges, including through a formal review of the legislation and the broader system.